The Islamic religion in prison and Moroccan women prisoners in Spain - Castillo-Algarra, Joaquina; Ruiz-García, Marta (’Ilu. Revista de Ciencias de las Religiones, 2024)
The main aim of this paper is to investigate how Moroccan women prisoners interpret and practice their religion in prison and the consequences of this in their lives, on an individual level and on a group level, in short the role religion plays for them in prison. Based on the qualitative method, and by using in-depth interviews as the investigative technique, the results show that, in general, religion brings important benefits such as psychological well being, helping the women prisoners to adapt to prison life, alleviating the pain of separation from their children and giving them hope for the future. However, the Islamic religion is the principal point of difference among the Moroccan women prisoners, according to the degree of influence that they exercise over each other which is influenced by various factors: where they come from, their socialization process and for the time that they have spent in prison. Based on these factors three distinct profiles for Moroccan women prisoners have been identified which differentiate them as women and as prisoners. In short, our results show that religion is key to understanding the identity of these women in prison. Our work opens a new line of investigation that encompasses religion, gender, nationality and prison not addressed until now.